Concomitant Recital of a Prolonged Reign: Dilation of the Dutch Empire and Enticement of Ascendency, Delineating Batavia, Victim and Valedictorian - KHALIL, SIEPAN; ZEID, PAKINAM (Alanya Üniversitesi, 2019)
The VOC (Verenigde Oost-Indische Compagnie) was both the absolutist and the pacifier as it sought to colonize Sunda Kelapa through the displacement of the indigenous population, architecture, and regimen; the VOC was deployed catalyst to the marking of a golden era, roughly spanning the 17th century through which architecture, trade, science, and military boomed, marking Jakarta a resilient harbour to the world's finest trades. Batavia, modern-day Jakarta, welded a myriad of names, endorsing its irrefutable paramount; one of which,